ผลของกลุ่มพัฒนาตนและการปรึกษาเชิงจิตวิทยาแนวพุทธเน้นศีลและปัญญาต่อสัมพันธภาพการปรึกษาเชิงจิตวิทยา และผลเนื่องต่อความพึงพอใจของผู้รับบริการ - ธีรวรรณ ธีระพงษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
This research was aimed to study the effect of Buddhist personal growth counseling group emphasizing SĪLA and PAÑÑĀ (BPGC) on counseling relationship of counselor-in-training and client satisfaction. Design of the research was the quasi experimental pretest-posttest control group design. The hypotheses were that (1) the BPGC group enhanced the counselor-in-training’s counseling relationship, (2) the BPGC group increased the scores on counseling relationship of the experimental group than the control group, and (3) the experimental group’ s scores on client satisfaction were higher than those of the control group. The sample was 16 volunteer counselors-in-training, and their 254 clients. The volunteer counselors were assigned based on availability to attend to either the experimental group or the control group, each of 8 persons. The experimental group participated in BPGC group conducted by the researcher for about 30 hours within 3 days. The instruments utilized were the counseling relationship inventory and the client satisfaction inventory constructed by the researcher. The counseling relationship was rated by three parties, i.e., the group members, the external rater who rated the quality of counseling relationship by listening to audio recordings, and the counselors-in-training. Data were analyzed by the ANOVA repeated measure, the t-test (independent group), and the MANOVA. The results reveal that: 1. The BPGC group enhances the counselor-in-training’s counseling relationship. 2. The experimental group’s scores on counseling relationship are higher than those of the control group. 3. The experimental group’s scores on client satisfaction are higher than those of the control group.